Green Synthesis and Characterization of ZnO Nanoparticles from Water Extract of Chenopodium Ambriosoides and Angelica glauca: A Comparative Analysis - Balam Bisht; Gunjan Karki; Pramod Khati (Journal of Water and Environmental Nanotechnology)
Since ancient times, zinc oxide has been a crucial industrial substance, and there is a lot of new interest in it these days. Its use in an incredibly wide range of industries has been ensured by a combination of physical properties like relatively high electrical and thermal conductivity, optical absorption, and very high-temperature stability, chemical properties such as stability at neutral pHs and mildly antimicrobial action, and techno-economic attributes such as easy availability and affordable price. The processes used to produce ZnO have continuously changed. In the present study, Nanoparticles of zinc oxide (Zn Nps) have been synthesized by a green chemistry approach using zinc acetate, sodium hydroxide, and water extract of Chenopodium ambriosoides and Angelica glauca. In this study, we report here a simple green technology to synthesize ZnO nanoparticles. Biologically synthesized Zn Nps characterized by UV-Vis spectral analysis, FT-IR, XRD, Scanning Electron Microscope (SEM), and Energy Dispersive X-ray Analysis (EDAX). The Zn Nps size obtained from water extract of Chenopodium ambriosoides and Angelica glauca have also been compared. Our result suggests that the water extract of Chenopodium ambriosoides is more suitable than the water extract of Angelica glauca for synthesizing ZnO Nps.